KAJIAN POTENSI DAN DAYA TARIK WISATA AIR TERJUN WAITATIRI DI NEGERI SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Joan Zevania Meyr Putinella; Henderina Lelloltery; Merlin Renny Sitanala (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Waitatiri Waterfall, located in Negeri Suli, Central Maluku Regency, represents a natural tourism destination with considerable ecotourism potential that remains suboptimally managed. This study aims to evaluate the capacity and distinctive features of Waitatiri Waterfall as a tourism destination in order to develop sustainable ecotourism development strategies. The research methodology encompasses field observations, comprehensive interviews with local government authorities and community members, as well as the collection of supporting documentation. Data analysis was performed using a descriptive approach that integrates both qualitative and quantitative dimensions, utilizing the Analysis of Natural Tourist Attraction and Object Operation Area (ADO-ODTWA) framework as the assessment instrument for development feasibility. The findings indicate that Waitatiri Waterfall possesses substantial natural resources, including six cascading waterfalls, natural pools, and rocky streams with picturesque landscapes. The area exhibits rich biodiversity, encompassing 19 flora species (including one protected/vulnerable species) and 12 fauna species (including two protected/threatened species). Based on the ADO-ODTWA analysis, Waitatiri Waterfall achieved a total score of 1170 with a feasibility rating of 81.25%, categorized as